A reduced fixed dose of Tocilizumab 200 mg compared to 400 mg in patients with severe COVID-19 disease (One Health & Risk Management, 2023)
Introduction. The deregulated excessive pro-inflammatory cytokine secretion have a detrimental impact on the evolution of COVID-19, aggregating the tissue impairment, organ failure, and increasing the risk for death. Several studies have demonstrated the beneficial effect of Tocilizumab (TCZ) in reducing hyperimmune response in severe forms of COVID-19.Materials and methods. This study is a retrospective cohort consisting of a sample of 66 patients hospitalised with COVID-19. The 1-st group consists of 33 patients treated with TCZ 200 mg IV once, and the 2-nd group – of 33 patients treated with TCZ 400 mg IV once.Results. The average age of the patients included in the study was 58,22±1,38 years. A decision regarding TCZ administration was made on average on the 11,34±0,31 day of the disease, when the beginning of Cytokine Storm was suspected in the patients already on dexamethasone treatment. The dose of TCZ had significance on the duration of patients' disabilities, duration of oxygen therapy, and duration of hospitalization, with better results for TCZ 400 mg vs. TCZ 200 mg. However, we cannot prove that the dose of TCZ influences the percentage of patients transferred to the ICU for invasive or non-invasive ventilation.Conclusion. The 200 mg fixed dose of TCZ can be a life-saving option for severely ill patients with COVID-19 in the context of IL-6 inhibitor supply shortages.
Keywords: COVID-19; Cytokine Storm; Tocilizumab